A Building The Renewable Independent Energy Village by Using Portable Digester Technology in Facing the 4.0 Industrial Era (GenBIoT) - Rais Rais; Arfan Haqiqi; Eko Budihartono; Rivaldo Mersis Brilianto (STEKOM PRESS, 2021)
The waste processing and renewable energy are being the issues in the industrial 4.0 era. Kitchen and organic trash in the rural areas will become a disaster if there is no solutions. On the other hand, kitchen and organic waste have a positive side, that they can be converted into biogas which can be converted into electricity. On the Minister of Energy and Mineral Resources Regulation Number 27 of 2014, supports the development of biogas and will buy electricity from the biogas conversion. The potential for biogas that obtained by the organic trash per 1000 people is 7619.8 liters of biogas, it meas that the energy contained is still abundant and the production can still be increased if processed with a modern digester system. This research produces a tool in the form of a portable digester that named GenBIoT (IoT-based Biogas Generator) which can be used by the public to produce biogas that used by home industries or general factories. This research used the research method that similar to System Development Life Cycle (SDLC), this tool is built with several stages starting from planning analysis, designing, functional testing, data analysis and reporting of the results or implementing this tool that can be used as an alternative, as a cheap and easy source energy. This tool is based on the Internet of Things so that this tool can be monitored regarding gas pressure in the reactor, biogas volume and it will detect if there is a biogas leak so it will displayed on the system. To produce the maximum biogas composition, 50% of cow dung is required, 40% of kitchen trash and 10% of water with a ratio of 5: 4: 1 so it will produce 40 kg of biogas with a volume of methane gas (VGM) 0.11 m3 of biogas for cow dung. and 0.04 m3. The third experiment becomes the basis of future biogas production with energy produced from biogas per day of 716.39 Wh